Challenge of Waqf to the Social and Economic Welfare of Muslim Communities: A Comparative Analysis Between Countries - Mujahidin Mujahidin; Muhammad Imran; Nasrullah Bin Sapa; Fasiha Fasiha; Sitti Aisya; Trimulato Trimulato (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Waqf is one of the important instruments in Islam that can contribute significantly to the social and economic welfare of the Muslim community. This study aims to analyze the challenges faced in the management of waqf in various countries and how these challenges affect the welfare of the Muslim community. This study uses a comparative approach by evaluating the policies, institutional structures, and practices of waqf management in several countries, including Indonesia, Malaysia, Turkey, and Egypt. The results show that although each country has different systems and regulations, there are common challenges such as lack of public awareness, lack of transparency, and limited institutional capacity. The study also identifies best practices that can be adopted to optimize the role of waqf in improving the social and economic welfare of the Muslim community